English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the answer is f(x)=-29+12n+n^2. but I don't understand how they got that. Please include steps.

2007-09-08 17:37:59 · 3 answers · asked by Angela T 1 in Science & Mathematics Mathematics

3 answers

Given f(x)=7-x^2
f(x)=6+n

So
f(x)=7-x^2 = 6+n

x^2 = 1+n

this is the answer you would get given the question the way you presented it.

The book may have specifically stated x = 6+n
In this case you substitute 6+n for x.

f(x)=7-x^2

f(x)=7- (6+n) ^2
Expand the square
f(x)=7- (36+ 12n + n^2)

f(x)=7- (36+ 12n + n^2)
f(x)=7- 36 - 12n - n^2
f(x)= - 29 - 12n - n^2

sometimes the book can be wrong!

2007-09-08 17:59:48 · answer #1 · answered by 037 G 6 · 0 0

f(x) = 7 - x^2, but x is also a function of n : f(x) = 6 +n

substitute (6+n) to x

f(x) = 7 - (6+n)^2
f(x) = 7 - (36 + 12n + n^2)
f(x) = 7 - 36 - 12n - n^2
f(x) = -29 - 12n - n^2 or -( 29 +12n + n^2)

2007-09-08 17:48:01 · answer #2 · answered by Enginurse 2 · 0 1

substitute in 6+n for x so the problem looks like f(n)=7-(6+n)^2 then simplify with FOIL to 7-36+6n+6n+n^2 then simplify againg to the answer 29+12n+n^2

2007-09-08 17:43:27 · answer #3 · answered by Quixotics92 2 · 0 1

fedest.com, questions and answers